Design features of a high-pressure transmission devices for hydro-jet technologies - V. I. Novikov; O. V. Kuzmin (Вестник СибАДИ)
Introduction. Hydro-jet technology is an innovative approach to using high pressure water for a variety of purposes. The technology has found a wide application in various industries, including construction, industry, agriculture and surface cleaning. The basic idea of water jetting systems is to use water as a powerful tool to destroy, clean and cut various materials. The paper discusses the constructing of the high-pressure hydro-puller device for hydro-jet technologies.Materials and methods. An analysis of the methods by hydro-jet technologies classification was made. The general structure and the constituent elements of this scheme is shown. Generalizing elements are identified and a characteristic layout diagram for use in all technological methods of hydro-jet methods is described, and the structural elements that are the main components and units of these technologies are described.Results. The scheme of energy flow on the main nodes of the traditional layout scheme of units for hydro-jet technologies is developed. The energy losses formed in the process of operation are estimated, the element of the hydrojet plant with the largest losses is determined, the peculiarities of its functioning and operation are analysed. The design methodologies, taking into account the identified problems and features, for high-pressure transmitting devices are given.Discussion and conclusions. The most efficient operation of ultra-high pressure transmitting devices for hydro-jet technologies is possible only taking into account their thermal state, characterized by a description of their thermal balance, which can only be ensured through the development of a number of techniques proposed for use in the design of such devices.